The analysis of gut microbiota in patients with bile acid diarrhoea treated with colesevelam - Kumar, Aditi; Quraishi, Mohammed Nabil; Al-Hassi, Hafid O.; El-Asrag, Mohammed E.; Segal, Jonathan P.; Jain, Manushri; Steed, Helen; Butterworth, Jeffrey; Farmer, Adam; Mclaughlin, John; Beggs, Andrew; Brookes, Matthew J. (Frontiers in Microbiology, 2023)
Introduction: Bile acid diarrhoea (BAD) is a common disorder that results from an increased loss of primary bile acids and can result in a change in microbiome. The aims of this study were to characterise the microbiome in different cohorts of patients with BAD and to determine if treatment with a bile acid sequestrant, colesevelam, can alter the microbiome and improve microbial diversity. Materials and Methods: Patients with symptoms of diarrhoea underwent 75-selenium homocholic acid (75SeHCAT) testing and were categorised into four cohorts: idiopathic BAD, post-cholecystectomy BAD, post-operative Crohn’s disease BAD and 75SeHCAT negative control group. Patients with a positive 75SeHCAT (<15%) were given a trial of treatment with colesevelam. Stool samples were collected pre-treatment, 4-weeks, 8-weeks and 6-12 months post-treatment. Faecal 16S ribosomal RNA gene analysis was undertaken. Results: 257 samples were analysed from 134 patients. -diversity was significantly reduced in patients with BAD and more specifically, in the idiopathic BAD cohort and in patients with severe disease (SeHCAT <5%); p < 0.05. Colesevelam did not alter bacterial /-diversity but patients who clinically responded to treatment had a significantly greater abundance of Fusobacteria and Ruminococcus, both of which aid in the conversion of primary to secondary bile acids. Conclusion: This is the first study to examine treatment effects on the microbiome in BAD, which demonstrated a possible association with colesevelam on the microbiome through bile acid modulation in clinical responders. Larger studies are now needed to establish a causal relationship with colesevelam and the inter-crosstalk between bile acids and the microbiome.